2018
DOI: 10.19080/artoaj.2018.14.555903
|View full text |Cite
|
Sign up to set email alerts
|

Physio Chemical Properties of Pomegranate Varitieas Collected from Peshawar Local Market

Abstract: The present study was conducted at the Agricultural chemistry Lab in the University of Agriculture Peshawar, Pakistan to evaluate the physico-chemical properties of two pomegranate verities: Bedana and kandahari. The colour, average weight, edible index and waste index of Bedana observed yellowish, 200.00g, 31.45% and 65.00% while of kandahari was dark red, 250.00g, 35.55% and 60.55% respectively. The average total soluble solid (TSS), reducing sugar, acidity, PH, moisture and ash of Bedana showed 150Brix, 7.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…As shown in Table 2, The pH value obtained for KH1 and HM1 is higher than some reported for Spanish, South African, Omani, Moroccan, Tunisian, Indian, Turkian, Iranian, Egyptian, Pakistani, Georgian pomegranate cultivars (Tehranifar et al, 2010;Ozlekci et al, 2011;Gadže et al, 2012;Caliskan & Bayazit, 2013;Ismail et al, 2014;Zaouay et al, 2014;Fernandes et al, 2017;Hota & Dahiya, 2017;Boussaa et al, 2018;Hmid et al, 2018;Usman et al, 2018;Díaz-Perez et al, 2019;Sassi et al, 2020;Meena et al, 2021;El Moujahed et al, 2022), while the pH value obtained for SL1 is closer to the values recorded on some Moroccan varieties such as "Jaune Marrakech" (Legua et al, 2011;Martínez et al, 2012), on Algerian cultivar "Doux de Koléa" (Meziane et al, 2016), on some Indian varieties such as Ganesh and Bhagwa (Hota & Dahiya, 2017) and on some pomegranate cultivars grown in Georgia (Díaz-Perez et al, 2019). Alcaraz-Mármol et al (2017) registered a higher pH than the reported values in the range of 6.02 to 6.78 for cultivars grown in Spain such as Mollar de Elche, Mollar de Orihuela and Valenciana de Albatera.…”
Section: Ph Titratable Acidity and Total Soluble Solidsmentioning
confidence: 59%
“…As shown in Table 2, The pH value obtained for KH1 and HM1 is higher than some reported for Spanish, South African, Omani, Moroccan, Tunisian, Indian, Turkian, Iranian, Egyptian, Pakistani, Georgian pomegranate cultivars (Tehranifar et al, 2010;Ozlekci et al, 2011;Gadže et al, 2012;Caliskan & Bayazit, 2013;Ismail et al, 2014;Zaouay et al, 2014;Fernandes et al, 2017;Hota & Dahiya, 2017;Boussaa et al, 2018;Hmid et al, 2018;Usman et al, 2018;Díaz-Perez et al, 2019;Sassi et al, 2020;Meena et al, 2021;El Moujahed et al, 2022), while the pH value obtained for SL1 is closer to the values recorded on some Moroccan varieties such as "Jaune Marrakech" (Legua et al, 2011;Martínez et al, 2012), on Algerian cultivar "Doux de Koléa" (Meziane et al, 2016), on some Indian varieties such as Ganesh and Bhagwa (Hota & Dahiya, 2017) and on some pomegranate cultivars grown in Georgia (Díaz-Perez et al, 2019). Alcaraz-Mármol et al (2017) registered a higher pH than the reported values in the range of 6.02 to 6.78 for cultivars grown in Spain such as Mollar de Elche, Mollar de Orihuela and Valenciana de Albatera.…”
Section: Ph Titratable Acidity and Total Soluble Solidsmentioning
confidence: 59%